Modelling human faces with non-contact three-dimensional digitizer-preliminary Results - Majid, Zulkepli; Setan, Halim; Chong, Albert K (Faculty of Geoinformation Science and Engineering, 2004)
Currently, there are several methods that can be used for modelling and measuring of human face such as digital stereo photogrammetry, phase measuring profilometry and others. These methods were employed in medical applications for the modelling of human face soft tissue and measurement and anthropometric landmarks. Both data are required for the development of a craniofacial database in craniofacial reconstructive surgery. In this paper, two laser scanners (i.e three dimensional non-contact digitizers) were used to produce a three-dimensional model of human faces and measure anthropometric landmarks. The process comprises of four steps: scanning of human face, three-dimensional image registration, three-dimensional modelling of human face and measurement and anthropometric landmarks. The obtained anthropometric landmarks measurement then compared with the conventional measurement method using callipers. This study shows that the used of laser scanning system in modelling human face was found to be excellent and efficient.